Protocol for the trial to establish a causal linkage between mycotoxin exposure and child stunting: a cluster randomized trial - Erica Phillips; Francis Ngure; Laura E. Smith; Edna Makule; Paul C. Turner; Rebeca Nelson; Martin Kimanya; Rebecca Stoltzfus; Neema Kassim (BMC Public Health, 2020)
Abstract Background The number of stunted children has fallen globally but continues to increase in Africa. Stunting is estimated to contribute to 14–17% of child deaths under 5 years of age and is a risk factor for poor cognitive and motor development and educational outcomes. Inadequate dietary intake and disease are thought to be the immediate causes of undernutrition and stunting. However, improving infant diets through complementary feeding interventions has been shown to only modestly reduce stunting. Multiple observational studies demonstrate a dose response relationship between fetal and post-natal aflatoxin exposure and reduced linear growth. Methods This community-based cluster randomized trial will measure the effect of a reduced aflatoxin diet on length-for-age Z scores at 18 months in central Tanzania. All 52 health facilities in the Kongwa District of Dodoma Region were randomized into two groups. Starting at 6 months of age, participants in the intervention group receive a low-aflatoxin pre-blended porridge flour containing maize and groundnut (ratio 4:1 respectively) and low-aflatoxin groundnut flour, whereas in the control group the same porridge mix and groundnut flour are promoted through education but acquired by the household. Both groups will receive the same infant and young child feeding education and a thermos flask. A total of 3120 infants between 6 weeks and 3 months of age will be recruited into the study over 1 year. Data will be collected four times – at recruitment and when the infants are 6, 12 and 18 months of age. In a cohort of 600 infants, additional data will be collected at 9 and 15 months of age. The primary outcome is length-for-age at 18 months. Secondary outcomes include the Z scores for weight-for-age, middle upper arm circumference and head circumference, and the blood biomarker aflatoxin-albumin in the full sample, with the urine biomarker aflatoxin M1 analyzed in the cohort only. Discussion Better understanding the etiology of childhood stunting can lead to more appropriate interventions and policies to further reduce linear growth faltering and meet the Sustainable Development Goals. Trial registration NCT03940547 , (April 24, 2019).